2007
DOI: 10.1086/510100
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria as an Agent for Change in Structural Plumage Color: Correlational and Experimental Evidence

Abstract: Recent studies have documented that a diverse assemblage of bacteria is present on the feathers of wild birds and that uropygial oil affects these bacteria in diverse ways. These findings suggest that birds may regulate the microbial flora on their feathers. Birds may directly inhibit the growth of harmful microbes or promote the growth of other harmless microbes that competitively exclude them. If keratinolytic (i.e., feather-degrading) bacteria degrade colored feathers, then plumage coloration could reveal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
116
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(124 citation statements)
references
References 50 publications
2
116
0
4
Order By: Relevance
“…Recent studies have shown that birds have distinctive feather bacteria that influence plumage condition and colouring [10,11,52], complex conjunctiva and nasal bacterial assemblages [53] and diet-determined differences in gut bacteria [6,23]. Microbial loads and assemblages often differ between bird species (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that birds have distinctive feather bacteria that influence plumage condition and colouring [10,11,52], complex conjunctiva and nasal bacterial assemblages [53] and diet-determined differences in gut bacteria [6,23]. Microbial loads and assemblages often differ between bird species (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…those that decompose keratin through keritinase production) can also be important in the Aves due to their likely role in feather degradation. Microbe-induced feather degradation can potentially hinder flight (when wing feathers are involved) and mate attraction (when plumage condition or colour is important for mate selection), as well as thermoregulation [10,11,52]; although the extent and magnitude of such effects is currently unknown [24]. Keratinolytic microbes previously associated with birds include the bacterium Bacillus licheniformis [47] and the fungi Chrysosporium tropicum and Microsporum gallinae [27].…”
Section: Introductionmentioning
confidence: 99%
“…Not only is it sensitive to developmental stress, but it is also affected by external factors like, for example, feather abrasion, the accumulation of dirt, and the presence of feather-degrading bacteria (e.g., Ö rnborg et al 2002;Shawkey et al 2007). UV coloration is thus, just like carotenoid-based coloration, assumed to reflect phenotypic quality (Keyser and Hill 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has shown that birds have distinctive plumage bacteria that can influence plumage colour and quality [10,11,59] and gut bacteria that vary according to diet both within and between species [6,18]. The importance, however, of microbial species on avian reproductive success, 56 offspring condition, and life-history traits is still poorly understood [10,35,36].…”
mentioning
confidence: 99%